2021
DOI: 10.1021/acsaem.1c01247
|View full text |Cite
|
Sign up to set email alerts
|

High-Specific-Capacity and High-Performing Post-Lithium-Ion Battery Anode over 2D Black Arsenic Phosphorus

Abstract: Nowadays, secondary batteries based on sodium (Na), potassium (K), and magnesium (Mg) stimulate curiosity as eventually high-availability, nontoxic, and eco-friendly alternatives of lithium-ion batteries (LIBs). Against this background, a spate of studies has been carried out over the past few years on anode materials suitable for post-lithium-ion battery (PLIBs), in particular sodium-, potassium- and magnesium-ion batteries. Here, we have consistently studied the efficiency of a 2D α-phase arsenic phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…Rapid ion mobility and fast electron transport are two required factors for achieving high rate capability. 69,102–104 In Section 3.1, we have found that the addition of BC 2 N to Black-Pn reduces its band-gap from 2.01 eV to 1.80 eV. Furthermore, the insertion of the Na atom improves the electrical conductivity of the hybrid BC 2 N/Blu-Pn system as we revealed in Section 3.2.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Rapid ion mobility and fast electron transport are two required factors for achieving high rate capability. 69,102–104 In Section 3.1, we have found that the addition of BC 2 N to Black-Pn reduces its band-gap from 2.01 eV to 1.80 eV. Furthermore, the insertion of the Na atom improves the electrical conductivity of the hybrid BC 2 N/Blu-Pn system as we revealed in Section 3.2.…”
Section: Resultsmentioning
confidence: 72%
“…The criteria to obtain the final charge product are the same as in our previously published work. 36 The corresponding average binding energy is computed according to the following expression 102 …”
Section: Resultsmentioning
confidence: 99%
“…128 More specically, multi-valent metal-organic batteries have also recently attracted signicant interest owing to their large availability as well as the high volumetric energy density of the multi-valent metals, such as Al, Mg, and Ca. [157][158][159] Besides their geo-political abundance over Li-atom, they also have higher volumetric-energy density by virtue of their multi electronic redox features. 160,161 Furthermore, the electrodes with multivalent metals show lower susceptibility to dendrite-growth, 162 and this is due to the signicantly shorter diffusion prole of multi-valent metals.…”
Section: Future Outlook: Multivalent Alkali Ion and Dissolution Issuementioning
confidence: 99%
“…11,12 Higher electronic conductivity, good cyclability, and significant specific storage capacity are crucial in the evaluation of the battery's performance. 13 Among carbon-based materials, graphite has been extensively used as an anode material in LIBs owing to its cycling stability, high energy stability, and low cost. 14 However, a low specific storage capacity of 372 mA h g −1 and structural disordering upon prolonged cycling limits its wide range of application.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-growing need for the next-generation LIBs can only be accomplished by the superior performance of the electrode materials. , Higher electronic conductivity, good cyclability, and significant specific storage capacity are crucial in the evaluation of the battery’s performance . Among carbon-based materials, graphite has been extensively used as an anode material in LIBs owing to its cycling stability, high energy stability, and low cost .…”
Section: Introductionmentioning
confidence: 99%